Convictions and ambivalences: theorizing power at a Cairene feminist NGO - Wulf, Laura (AUC Knowledge Fountain, 2011)
In this project, I attempt to conduct an “ethnography of theory” among women activists in an Egyptian feminist non-governmental organization (NGO). In doing so, I follow the calls for grounding theory of gender and the Middle East in day-to-day lived experience, through ethnography rather than “polemic” (L. Abu-Lughod 2010). This model takes women to be active participants in the creation of their own subjectivities and focuses on the analytic frameworks they employ in understanding this process. The Cairene feminist NGO, New Woman Foundation (NWF), is a forum for a range of professionals, young students, and activists who together encompass a range of experiences and perspectives on feminist work. In particular, I examine interpretations of discourses and institutions of power and a woman’s navigation therein. As I describe, power is understood to manifest and function in various forms, through human rights and feminism, the family, the state, and in the structure of NGO work itself. This project analyzes the changing, often complex and contradictory, individual frameworks that women employ in their reflections upon such forces. All in all, a dual set of strong convictions and ambivalences come to characterize women’s perceptions of their work. As this project’s participants continuously reassert the necessity of intellectual and moral commitment to women’s rights, they simultaneously must in some way come to terms with the limitations and contradictions in their work. Through analyzing these different groups of women’s reflections on their work, I locate the daily experiences and contemplations of NWF participants in wider debates on feminism in the MENA region.